If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 + 4x = -3 Reorder the terms: -3 + 7x + 4x = -3 Combine like terms: 7x + 4x = 11x -3 + 11x = -3 Add '3' to each side of the equation. -3 + 3 + 11x = -3 + 3 Combine like terms: -3 + 3 = 0 0 + 11x = -3 + 3 11x = -3 + 3 Combine like terms: -3 + 3 = 0 11x = 0 Solving 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 0 Simplifying x = 0
| 3x+3=-6+6x | | 4x+28=10x-33 | | 4y-10=5y-15 | | 12y=-4(y+1) | | 4t^3-t=0 | | 138=-6x+5(x+26) | | d=120-4t | | 0.02x=0.45 | | 0.98x=0.45 | | 285=-7x-6(-5x-13) | | 2(k-4)=6 | | 11p=5p+2(10p-7) | | x*x+2*x+9=0 | | 2x=78+1 | | 2a/18ab | | h=-4.9t^2+50t+80 | | x*x*x*4+93*x*x+200*x+1000=0 | | -4(-7x+8)=-32 | | 2x+39=x-10 | | 4x-16=15x | | Z^2+2z+1=2i | | 4x^2+5=53 | | -10=-7x-17/8 | | 0.3=p-250 | | 10y=-5x+12 | | 4y+8y=180 | | 13/r=-12/13 | | -6x+7=7x-19 | | 3=a/5-9 | | 4x+7(-4x-28)=20 | | 19y+43=81 | | -824=8(-15x+2) |